Diversity and Introduction History of Glycaspis brimblecombei Reflects a History of Bridgeheads and Distinct Invasions - Dittrich-Schröder, Gudrun; Garnas, Jeff R.; Arriagada-Cares, Daniela; Ahumada, Rodrigo; Hurley, Brett P.; Lawson, Simon A.; Slippers, Bernard (Frontiers in Forests and Global Change, 2021)
Glycaspis brimblecombei is an invasive insect pest of Eucalyptus that has spread rapidly around the world since its first report in California in 1998. The pest now occurs on at least four continents where Eucalyptus is grown as a non-native plantation species. To characterise global routes of invasion for this insect, we characterised the sequences of a portion of the Cytochrome Oxidase 1 (COI) gene from 105 individuals from the invasive and native range, including from Australia, Brazil, Chile, La Réunion, Mauritius, South Africa and the USA. In addition, we developed 13 polymorphic microsatellite markers, of which we used 11 to characterise the diversity in the same 105 specimens. Our results suggest that there have been two independent introduction events from Australia, which is assumed to be the origin, to distinct parts of the adventive range. The first introduction was into the USA, from where it appears to have spread to South America and eventually to South Africa. This finding highlights the threat of bridgehead populations to accelerate pest invasions in Eucalyptus, even if those populations are on widespread non-commercial populations of Eucalyptus (as in California). A second introduction appears to have occurred on the islands of Mauritius and La Réunion and provides another example of the establishment of independent lineages of invasive global insect pests. This complex invasion pattern mirrors that found in other Eucalyptus pests.